Genetic diversity is largely unpredictable but scales with museum occurrences in a species-rich clade of Australian lizards. Issue 1854 (3rd May 2017) - Singhal, Sonal; Huang, Huateng; Title, Pascal O.; Donnellan, Stephen C.; Holmes, Iris; Rabosky, Daniel L.
Abstract : Genetic diversity is a fundamental characteristic of species and is affected by many factors, including mutation rate, population size, life history and demography. To better understand the processes that influence levels of genetic diversity across taxa, we collected genome-wide restriction-associated DNA data from more than 500 individuals spanning 76 nominal species of Australian scincid lizards in the genus Ctenotus . To avoid potential biases associated with variation in taxonomic practice across the group, we used coalescent-based species delimitation to delineate 83 species-level lineages within the genus for downstream analyses. We then used these genetic data to infer levels of within-population genetic diversity. Using a phylogenetically informed approach, we tested whether variation in genetic diversity could be explained by population size, environmental heterogeneity or historical demography. We find that the strongest predictor of genetic diversity is a novel proxy for census population size: the number of vouchered occurrences in museum databases. However, museum occurrences only explain a limited proportion of the variance in genetic diversity, suggesting that genetic diversity might be difficult to predict at shallower phylogenetic scales.